Spectroscopic analysis of chrysotile asbestos and its environmental resistance in asbestos cement waste products - Zoltán Macher, Gergely; Károly, Fanni; Teh, Christopher Boon Sung; Beke, Dóra; Torma, András; Gergely, Szilveszter (Universiti Putra Malaysia Press, 2024)
Most asbestos-related studies have focused on asbestos exposure risks, their associated health implications, and waste management issues. Our research introduced a unique perspective that has rarely been explored: the impact of environmental factors on asbestos cement products. The novelty of the study is that, in contrast to previous research, in addition to determining the material quality of asbestos, it analyses the trace materials, additives and the emissive nature of chrysotile fibers. This study aims to identify the chrysotile-asbestos content in three common asbestos cement products found in Hungary, with regard to the release of their fibers upon exposure to the environment and to identify trace elements that could be used to identify the origin and function of each of these products. Our analyses revealed the presence of chrysotile in each tested sample, with spectral matches ranging from 59.6% to 86.7%. Asbestos cement products exposed to various environmental influences for long periods showed a greater chrysotile emission capacity than those unexposed or hermetically sealed ones. Additionally, we established that all asbestos cement products contained glass fibers, with an average spectral match of 62.1%. We further identified polysilicate in the materials with an average spectral match of 66.0%, as it was included in asbestos cement products to enhance their heat resistance. Our results pave the way for a new methodology for assessing asbestos cement products with regard to the implementation of their trace element level assessments.